فاعلية استخدام استراتيجيتي ميرل-تنسون والخارطة الدلالية في تحصيل بعض مفاهيم طرائق التدريس لطلاب كلية التربية البدنية وعلوم الرياضة - أحمد، أحمد منذر جهاد Ahmed, Ahmed Mundher Jehad; يونس، أفراح ذنون; عبدالله، طلال نجم (جامعة تكريت - كلية التربية البدنية وعلوم الرياضة, 2017)
هدف البحث إلى: الكشف عن أثر استخدام استراتيجيتي ميرل- تنسون والخارطة الدلالية في إكساب بعض مفاهيم طرائق التدريس لدى طلاب كلية التربية البدنية وعلوم الرياضة، ومعرفة أيهما أفضل. وافترض الباحث ما يأتي: لا توجد فروق ذات دلالة إحصائية بين متوسط درجات طلاب المجموعة التجريبية الأولى التي تدرس وفق استراتيجية ميرل- تنسون، وبين متوسط درجات طلاب المجموعة التجريبية الثانية التي تدرس وفق استراتيجية الخارطة الدلالية في اختبار تحصيل مفاهيم طرائق التدريس. تكونت عينة البحث من(56) طالبا من طلاب السنة الدراسية الثالثة في كلية التربية البدنية وعلوم الرياضة بجامعة تكريت للعام الدراسي (2016-2017)، توزعوا على مجموعتين تجريبيتين، حيث درست المجموعة الأولى وفق استراتيجية ميرل- تنسون، أما المجموعة الثانية فقد درست وفق استراتيجية الخارطة الدلالية، وتم تحقيق التكافؤ لمجموعتي البحث في متغيرات (العمر الزمني، والتحصيل الدراسي في المرحلة السابقة). بعدها تم تطبيق التجربة واستغرقت (8) أسابيع، تلقى فيها طلاب عينة البحث (16) وحداة تعليمية، وقد طبق الباحث اختبارا تحصيليا مقننا، واستخدم الباحث عددا من الوسائل الإحصائية، وهي ضمن الحقيبة الإحصائية (SPSS)، لإجراء التكافؤ بين مجموعتي البحث، ولبيان الفروق بين مجموعتي البحث. أظهرت النتائج تفوق المجموعة التجريبية الثانية التي درست وفق استراتيجية الخارطة الدلالية على المجموعة التجريبية الأولى التي درست وفق استراتيجية ميرل- تنسون في إكساب بعض مفاهيم طرائق التدريس. استنتج الباحث ما يأتي: 1. نجاح استراتيجيتي ميرل- تنسون والخارطة الدلالية في إكساب بعض مفاهيم طرائق تدريس التربية البدنية وعلوم الرياضة للمرحلة الثالثة. 2. تفوق استراتيجية الخارطة الدلالية على استراتيجية ميرل- تنسون في إكساب بعض مفاهيم طرائق تدريس التربية البدنية وعلوم الرياضة للمرحلة الثالثة. وفي ضوء هذه النتائج أوصى الباحث بما يأتي: 3. إجراء دراسات أخرى تستخدم نماذج واستراتيجيات غير الاستراتيجيات قيد الدراسة، لمعرفة مدى فاعليتها في إكساب مفاهيم طرائق التدريس لطلاب كلية التربية البدنية وعلوم الرياضة،. 4. إجراء دراسات أخرى وباستخدام استراتيجيتي ميرل- تنسون والخارطة الدلالية على عينة من الطالبات لنفس المرحلة ولنفس المادة التعليمية ومعرفة نسبة التطور لديهن، ومقارنة نتائجهن مع نتائج الطلاب والتعرف على الفروق بينهما. The objectives: Using Miller- Tynson and indicative map two strategies in acquiring some concepts of the teaching methods of College of Sport Education. the researcher proposed the following: There are no statistical indicative differences between the average of the students' scale of the first experimental group which studies Miller – Tynson strategy and the average of the students of the second experimental group which studies indicative map strategy in the test of concepts of teaching methods. The number of the sample is (56) students, consists of the third year students at the College of Sport Sciences and Physical Education at the University of Tikrit (2016-2017), distributed into two experimental groups, The first group studied according to Miller – Tynson strategy and second group according to the indicative map, and the equivalence had been achieved for the research groups in variables (the chronological age, and Educational level in previous years). The experiment took 8 weeks and the students have studied (16) According to the results the researcher has concluded: 1. Success of the Miller-Tynson strategy and indicative map in acquiring some concepts in teaching methods of the sport sciences and physical education for third year students. 2. Superiority of the indicative map strategy against Miller-Tynson strategy in getting some concepts in teaching methods of the sport sciences and physical education for third year students Recommendations 1. Adopting the two educational samples according to Miller- Tynson and indicative map in developing of innovative thinking for the students of the college of Physical Education and Sport Sciences. 2. Providing a suitable educational environment for developing the innovative thinking and other types of thinking inside the classrooms by developing the innovation, cooperation, respecting the others' opinion, encouraging of search and providing the necessary financial capacity. Suggestions:- 1. Conducting other studies by using modern strategies and samples other than the strategies used by studies in order to know the range of its activity in studying of the concepts of the teaching methods for the students of the physical education and sport sciences. 2. Conducting other studies by using Miller- Tynson and indicative map on a female students and for the same stage and subject, and checking the percentage of the their development their results comparing with the male students.
Keywords: التعليم الجامعي -- استراتيجية ميرل-تنسون -- استراتيجية الخارطة الدلالية -- طرائق التدريس -- التربية الرياضية